Типіфікація видів родини Salicaceae Lindl., описаних із території України - Оптасюк, О.М.; Шевера, М.В. (Український ботанічний журнал, 2011)
Представлены результаты типификации таксонов семейства Salicaceae Lindl., описанных с территории Украины (семь лектотипов — Populus pannonica Kit. ex Besser, Salix canaliculata Besser, S. pocutica Zapał. var. polesica Zapał., S. polesica Zapał., S. sarmatica Zapał., S. volhyniensis Zapał., S. wołoszczakii Zapał.; один голотип — S. pocutica Zapał.). Для каждого вида указаны номенклатурная цитата, основная синонимика, категория типа (лектотип, голотип, автентичный образец), авторы, выделившие его, место хранения; есть критические заметки. The paper reports results of the typification of the species of the familiy Salicaceae Lindl. described from Ukraine (seven lectotypes, Populus pannonica Kit. ex Besser, Salix canaliculata Besser, S. pocutica Zapał. var. polesica Zapał., S. polesica Zapał., S. sarmatica Zapał., S. volhyniensis Zapał. and S. woloszczakii Zapał.; one holotype, S. pocutica Zapał.). For each species, the following data are provided: basionym, main synonyms, category of type (lectotype, holotype, authentic specimen), original nomenclatural citation, herbarium of deposit, and critical notes.